Identification of avian remains contained within wrapped ancient Egyptian mummies: Part 1, A critical assessment of identification techniques. (October 2022) - McKnight, Lidija; White, Judith; Rosier, Amy; Cooper, Joanne; Bibb, Richard
Highlights: A targeted study of bird remains mummified as offerings to the gods in ancient Egypt. An experimental study to investigate the difficulties encountered when attempting to identify incomplete and comingled bird remains within wrapped mummy bundles. A comparative study evaluating experts' opinions of bird identification using radiographic modalities (X-ray and CT scanning) compared to bone-in-hand identification of physical bird bones. Abstract: Ancient Egyptian bird mummies manufactured in huge numbers present a unique and intriguing body of material with great archaeological and zooarchaeological significance. Research into this ancient practice is gaining momentum; however, one area that lacks clarity, but that is vital for the accurate interpretation of mummies as objects of ritual significance, is our ability to proffer accurate identifications of remains contained within wrapped mummy bundles. This is particularly relevant in the case of bird mummies where morphological variation between species can be minimal. This paper presents the results of a multi-faceted research project combining non-invasive radiographic modalities, experimental techniques and 3D replication, designed to assess the accuracy of avian skeletal identification when physical access to the bones themselves is not possible.